2016
DOI: 10.1111/jvs.12416
|View full text |Cite
|
Sign up to set email alerts
|

Species composition determines resistance to drought in dry forests of the Great Lakes – St. Lawrence forest region of central Ontario

Abstract: Question: Predicted changes in the frequency of short-term drought events raise concerns about potential effects of climate change on forest ecosystems. Few experiments have investigated the effects of tree species richness and composition in forest assemblages exposed to drought, and general conclusions for these systems are currently lacking. We tested the hypothesis that different species richness and composition affects community-level stability during a severe short-term drought event across a gradient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Comparisons between managed forests and their counterpart natural forests also revealed that their response to the same extreme event could be opposite (van Gorsel et al, ; Zald & Dunn, ). Other studies have indicated that resistance of forests to climate extremes is determined by the species composition and stand density (Arthur & Dech, ; Giuggiola, Bugmann, Zingg, Dobbertin, & Rigling, ). Natural forests with lower density, higher structural complexity, and more understory tend to be more resilient to climate anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between managed forests and their counterpart natural forests also revealed that their response to the same extreme event could be opposite (van Gorsel et al, ; Zald & Dunn, ). Other studies have indicated that resistance of forests to climate extremes is determined by the species composition and stand density (Arthur & Dech, ; Giuggiola, Bugmann, Zingg, Dobbertin, & Rigling, ). Natural forests with lower density, higher structural complexity, and more understory tend to be more resilient to climate anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of drought, as the total sum of areas across z-scores, exhibited different patterns in different years, leading to varied responses of different forest types to the climatic anomalies. Impact of drought on forests can vary largely depending on the forest type, tree species, and factors that are controlled by species composition, and past exposure to extreme conditions (Arthur and Dech 2016;Chen et al 2022). Our analysis showed that conditions in summer 2022 reduced vegetation functioning across DBFs the most, as it was indicated by declined SIF signals (Figure 5).…”
Section: Canopy Response To Drought Across Different Forest Typesmentioning
confidence: 67%
“…Our findings agree with other studies (e.g., Irvine et al 2002 ; Yang et al 2010 ; Gao et al 2017 ; Chen et al 2020b ; Duffy et al 2021 ) and further imply that mature forests are more resilient to drought stresses. It is also likely that long-term forest management activities, such as selective thinning, may have increased the forest’s resilience to drought by reducing stand density (Giuggiola et al 2013 ) or by introducing more drought resistant secondary deciduous species (Arthur and Dech 2016 ). Our results imply that the more frequent climate extremes in the future may have a profound impact on forest carbon sink in managed temperate forests, as the most productive middle aged forest are the most sensitive to heat and drought stresses.…”
Section: Discussionmentioning
confidence: 99%